Fenomena Bunuh Diri dalam Terang Dokumen Gereja untuk Memahami Tujuan Hidup Manusia Kristiani bersama Kristus - Kurniawan, Ambrosius Armando Sakti (Institutum Ioannis Mariae Vianney Surabayanum, 2025)
The phenomenon of suicide is increasingly common among students and it also occurs in several universities in Surabaya. What actually happened that made these students dare to do such actions? The author sees that this phenomenon is related to a person's self-existence, including identity crisis, emotional disstress, void in the meaning of life. From the perspective of the Catholic Church, human life has an ultimate goal, which is to unite with Christ. Church documents such as Spe Salvi and Veritatis Splendor help a Christian to see that true happiness does not lie in worldly satisfaction, but in a relationship with God and the hope of eternal life. The Catholic Church offers a transformative solution to this existential crisis, by inviting humans to understand the meaning of misery in the light of the cross of Jesus Christ and finding true happiness in faith and love for God.